Gonad transcriptome analysis reveals the differences in gene expression related to sex-biased and reproduction of clam Cyclina sinensis - Liu, Meimei; Ni, Hongwei; Rong, Zichao; Wang, Zi; Yan, Susu; Liao, Xiaoting; Dong, Zhiguo (Frontiers in Marine Science, 2023)
Sexual differentiation and gonad development are important biological processes for bivalve species. The clam Cyclina sinensis is an important cultured marine bivalve widely distributed along with the coastal areas of China. However, the information related to sexual determination/differentiation and gonadal development of C. sinensis almost has no reported. To study the molecular mechanisms of its sexual determination/differentiation and gonadal development, transcriptome analysis was performed in the gonad of C. sinensis, and the potential biological functions of reproduction-related gene were also investigated in this study. The results showed that 1 013 and 427 genes were differentially expressed in the ovary and testis, respectively. KEGG enrichment analysis showed that the DEGs in the gonad were significantly clustered in progesterone-mediated oocyte maturation, cell cycle and oocyte meiosis. Further analysis showed that 23 genes were mainly involved in sex determination/differentiation, including Dmrt1, Sox2/4/9, Foxl2, β-catenin and GATA-type zinc finger protein 1-like. Twenty key genes were mainly involved in the process of spermatogenesis, and five genes encode steroid biosynthesis and metabolism. Fifteen genes related to ovarian development were also identified in this study, such as Vitellogenin, MAM and LDL-receptor class A domain-containing protein 1 and Cell division cycle protein 20 homolog. Moreover, 50µg/L estradiol treatment significantly up-regulated the expression levels of CsVg in the ovary and hepatopancreas. These results highlight the genes involved in sexual determination/differentiation and gonadal development, which enhance our understanding for further studies of reproduction and breeding of C. sinensis and other marine bivalves.